Opportunities and barriers for young rural–urban migrants transitioning from education to work in Kathmandu, Nepal. Issue 1 (1st January 2021) - Basnet, Neha; Timmerman, Margaretha C.; van der Linden, Josje
ABSTRACT: This paper explores the opportunities and barriers encountered by young rural–urban migrants as they transition from education to work in Kathmandu, Nepal. It explores the opportunities available to both male and female youth during their transition from education to work and how these opportunities positively influenced their trajectories. On the other hand, the study also presents the barriers experienced by both male and female youth that may have negatively influenced their education-to-work transition processes. Qualitative interviews conducted with 24 participants show that parents' choices in education, migration to Kathmandu for education or work, going abroad for studies and work, and financial resources were the main experiences of opportunities and barriers influencing their trajectories. Using comparative analysis, gender differences in opportunities and barriers were found among the participants.